2017
DOI: 10.1186/s12911-017-0536-z
|View full text |Cite
|
Sign up to set email alerts
|

Communicating projected survival with treatments for chronic kidney disease: patient comprehension and perspectives on visual aids

Abstract: BackgroundMortality in end stage renal disease (ESRD) is higher than many malignancies. There is no data about the optimal way to present information about projected survival to patients with ESRD. In other areas, graphs have been shown to be more easily understood than narrative. We examined patient comprehension and perspectives on graphs in communicating projected survival in chronic kidney disease (CKD).MethodsOne hundred seventy-seven patients with CKD were shown 4 different graphs presenting post transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
1
1
1
Order By: Relevance
“…Our results also have similarities with an earlier Australian study finding that a large proportion of middle-aged women with breast cancer wanted verbal prognostic information summarized in written format, where words were preferred over numbers [ 22 ]. Contrary to our study, a recent study in patients with end-stage renal disease found the use of graphical formats for survival outcomes to be highly favoured and useful [ 23 ], and another inpatient study of > 75-year-olds reported that the pictorial representation of probabilities was positively received [ 24 ]. Cultural differences and education may explain this variation in preferences, but our pilot sample did not intend and did not allow for statistical exploration of these factors.…”
Section: Discussioncontrasting
confidence: 98%
“…Our results also have similarities with an earlier Australian study finding that a large proportion of middle-aged women with breast cancer wanted verbal prognostic information summarized in written format, where words were preferred over numbers [ 22 ]. Contrary to our study, a recent study in patients with end-stage renal disease found the use of graphical formats for survival outcomes to be highly favoured and useful [ 23 ], and another inpatient study of > 75-year-olds reported that the pictorial representation of probabilities was positively received [ 24 ]. Cultural differences and education may explain this variation in preferences, but our pilot sample did not intend and did not allow for statistical exploration of these factors.…”
Section: Discussioncontrasting
confidence: 98%
“…In our study, participants described challenging consultation experience about exchanging necessary self-referral information, align with previous studies reported poor consultation experience for long-time waiting and rush discussion [39]. [40]. Participants denied they master communication tips and skills, which re ected systematic training should be organized.…”
Section: Discussionsupporting
confidence: 82%
“…Icon arrays, graphics that use icons in grids to represent "at risk" populations (usually in proportion to the whole population), are among the most common visualizations in modern risk communication practice and scholarship. Many studies show that they can increase risk comprehension and avoidance actions (Ancker et al 2011;Dowen et al 2017;Tubau et al 2019;Galesic et al 2009;Garcia-Retamero et al 2010;Garcia-Retamero and Galesic 2009;Keller and Siegrist 2009;Schirillo and Stone 2005;Garcia-Retamero and Cokely 2014;Garcia-Retamero and Galesic 2010;Leonhardt and Robin Keller 2018;Stone et al 1997;Taylor et al 2018;Witteman et al 2014;Zikmund-Fisher et al 2014. While there are many mechanisms that relate icon arrays to risk comprehension and action, many scholars theorize that they are effective because they communicate risk information in ways that show exact percentages while simultaneously conveying "gist" impressions (Hawley et al 2008;Hess et al 2011).…”
Section: Visualizations (I) Visualizations In Non-weather Domainsmentioning
confidence: 99%